Some Basic Existential-Phenomenological Research Methodology for Counsellors - Osborne, John W. (Canadian Journal of Counselling and Psychotherapy, 2011)
This paper describes the major characteristics of existential-phenomenological research methodology for counsellors. The following topics are discussed: philosophical foundations, formulating the question, selection of participants, bracketing, data sources, data analysis, reliability and validity. The similarity of qualities needed for success as a counsellor and existential phenomenological researcher are presented as a basis for advocating their integrative practice.